MOOC Integration into Secondary School Courses - Najafi, Hedieh; Evans, Rosemary; Federico, Christopher (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
We investigated how high school students taking a university preparatory economics course would engage with the learning and assessment components of a Behavioural Economics MOOC that was integrated into their school-based course. Students were divided into two groups, MOOC-only, with no teacher support, and blended-mode, with weekly tutorials. MOOC only students scored slightly lower on a teacher designed knowledge test but scored slightly higher in a MOOC test. Although the MOOC-only students watched more unique videos, the blended-mode students stayed more on-track with the MOOC. The blended-mode students showed more persistence in retaking quizzes, yet they scored lower than the MOOC-only students.